Pengaruh Penggunaan Perpustakaan Sekolah dan Pojok Baca Terhadap Minat Belajar Peserta Didik pada Mata Pelajaran Akidah Akhlak: The Effect of Using the School Library and Reading Corner on Students' Learning Interest in Akidah Akhlak Subjects - Afia, Selfa; Saprin; Rasyid, Muhammad Rusdy (CV. Kalimasada Group, 2024)
This research aims to analyze how much influence the use of the school library and reading corner has on students' interest in learning in the subject of moral beliefs at MI Manggarupi. This type of research is ex post facto research with a quantitative approach and a scientific approach through pedagogical and psychological approaches. There were 203 respondents in this study using a sample of 40 people using a simple random sampling technique which used a questionnaire instrument to obtain data which was analyzed using descriptive and inferential statistical techniques. Hypothesis testing uses a simple linear regression test simultaneously through multiple linear regression tests. The results of this research show that the use of the school library affects students' interest in learning in the subject of moral beliefs at MI Manggarupi with a simple linear regression equation, namely Y = 31.40 + 0.58X. Then the use of reading corners on students' interest in learning in the subject of moral beliefs at MI Manggarupi with a simple linear regression equation, namely Y = 5.51 + 1.18X. Furthermore, there is a simultaneous influence between the use of the school library and reading corners on students' interest in learning in the subject of moral beliefs at MI Manggarupi with a multiple linear regression equation, namely Y = = 0.32+ 0.27X1+ 1.67X2 and the level of influence is 96.5% and the rest is influenced by other factors.